Moisture gains from evaporation as a design parameter for the ventilation system of indoor swimming pools - Przybylak , Jagoda; Ratajczak , Katarzyna (Instal, 2019)
Moisture gains from evaporation are an important parameter affecting the design of a ventilation system in indoor swimming pools. There are many formulas available in the literature for calculating the amount of moisture gain.  It may be difficult to choose the right one. The analyzes presented are intended to show what is the impact of the choice of formula to calculate moisture gains on the size of ventilation ducts, i.e. the investment costs of the installation. The formulas for calculating the moisture gains were reviewed, three recommended in the literature were selected and the supply air stream was determined as well as the size of ventilation ducts and the ventilation unit. The results show that by choosing different formulas for determining moisture gains, the costs of ventilation ducts and air handling units used in an example pool facility may vary in extreme cases even up to five times. It has been shown that the adoption of the average value of moisture gains results in excessive results in relation to the amount of evaporating water measured in real facility. Due to the multiplicity of formulas for determining moisture gains in indoor pools, the applied formula needs to be carefully chosen, because moisture gains are a very important design parameter that affects investment and operating costs.
Keywords: evaporation; moisture gains; swimming pool ventilation